Kathrine Finley: capstone - Finley, Kathrine, artist (Colorado State University. Libraries, 2015)
The artist's statement: As an artist, I am inspired by the dualities of the intangible and tangible world. I have always been perplexed by what we find visually pleasing collectively, as well as individually. What one person finds beautiful may be dreadful to another, yet there are certain things that can be unanimously seen as pleasing in general. There are, also, certain intersections of beauty/safety and ugliness/danger, which we can't decipher as either or. In my most recent body of work I have been exploring the natural world and how certain elements of it can exhibit these dichotomies. I have been investigating the natural world in hopes that I can draw the viewer closer, in order to see the tiny space, as well as push the viewer outward to see the vastness of space as a whole. I am working with very small viewing windows that represent the shapes and patterns of our world either in an extreme close up, or macro view. I am interested in abstracting our world through a type of viewing window, either extremely zoomed in or expanded outward. My aim with this series is to engage with imagery that is ambiguous. I want to portray scenes that may not be readily recognizable, yet still can be comprehensible as something environmental. I want each piece to be able to stand alone, but like parts of an eco-system that work together, I want these pieces to be experienced symbiotically. In creating these pieces, I have been implementing an ancient form of printmaking, which utilizes carved woodblocks as the printing matrix. I chose to work with woodcuts for the reason that these prints have traditionally held a close connection to nature, focusing on the curiosities of our world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.